Stranger – Ger - Armin Langer (St Andrews Encyclopaedia of Theology)
The commandment to protect the ger, often translated as stranger, is asserted several times in the Torah. The book of Exodus requires the Israelites ‘not to do wrong to a ger or oppress them’ (22:21). Leviticus teaches that a ger who resides with Israelites shall be treated as an Israelite citizen, and that the people of Israel should have ‘one standard for ger and citizen alike’ (24:22). But what exactly is a ger? Throughout the centuries, Jewish tradition has offered various meanings of this biblical concept. The early Rabbis distinguished between ger tzedek (‘righteous alien’), that is, a non-Jew who becomes a Jew through conversion, and a ger toshav (‘resident alien’), that is, a non-Jew who lives among Jews and accepts the Noahide Commandments (Gen 9:8–17). Some leading Rabbis like Rashi argued that ger applies first to these Noahides. Others, like Maimonides, understood ger most of all as a reference to converts, since Jews did not form the majority in any society and therefore did not have the chance to oppress anybody except converts. Some contemporary Orthodox Rabbis in Israel apply the term to local Arab and Palestinian populations, while other Liberal Rabbis in the US use it to describe non-Jewish fellow travellers. This article will present the evolution of the term ger from the Bible through Rabbinic times, introduce the reader to some of the traditional debates on the figure of the ger, and finally discuss the modern applications of the term. But first, it will present the etymology of the Hebrew word ger.